Interpersonal Relationships : professional communication skills for nurses / Elizabeth C Arnold, Kathleen Underman Boggs - Arnold, Elizabeth C
Offers practical guidance for effective interactions with clients, colleagues, and families. This book provides information on communication skills for nurses, combining proven communication strategies and nursing principles with psychology and related theoretical frameworks. It includes numerous experiential exercises to evaluate their skills.